Mechanisms of SARS-CoV-2 Transmission and Pathogenesis - Harrison, Andrew G. (Trends Immunol, 2020)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) marks the third highly pathogenic coronavirus to spill over into the human population. SARS-CoV-2 is highly transmissible with a broad tissue tropism that is likely perpetuating the pandemic. However, important questions remain regarding its transmissibility and pathogenesis. In this review, we summarize current SARS-CoV-2 research, with an emphasis on transmission, tissue tropism, viral pathogenesis, and immune antagonism. We further present advances in animal models that are important for understanding the pathogenesis of SARS-CoV-2, vaccine development, and therapeutic testing. When necessary, comparisons are made from studies with SARS to provide further perspectives on coronavirus infectious disease 2019 (COVID-19), as well as draw inferences for future investigations.